2022
DOI: 10.3390/cells11132025
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Regulators in Neutrophils

Abstract: Neutrophils are the most abundant leukocytes in humans and are critical for innate immunity and inflammation. Integrins are critical for neutrophil functions, especially for their recruitment to sites of inflammation or infections. Integrin conformational changes during activation have been heavily investigated but are still not fully understood. Many regulators, such as talin, Rap1-interacting adaptor molecule (RIAM), Rap1, and kindlin, are critical for integrin activation and might be potential targets for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 249 publications
0
4
0
Order By: Relevance
“…The activation of Rap1 also promotes HeLa cell migration 27 . Previously, it was reported that activation of Rap1 also plays a key role in integrin mediated inside‐out signaling, increases cell adhesion, and is involved in the formation of focal adhesions, cell junction and cell proliferation 9,28 . Rap1 localization in the cell is responsible for activation; it is also localized to the plasma membrane 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of Rap1 also promotes HeLa cell migration 27 . Previously, it was reported that activation of Rap1 also plays a key role in integrin mediated inside‐out signaling, increases cell adhesion, and is involved in the formation of focal adhesions, cell junction and cell proliferation 9,28 . Rap1 localization in the cell is responsible for activation; it is also localized to the plasma membrane 29 …”
Section: Discussionmentioning
confidence: 99%
“…27 Previously, it was reported that activation of Rap1 also plays a key role in integrin mediated inside-out signaling, increases cell adhesion, and is involved in the formation of focal adhesions, cell junction and cell proliferation. 9,28 Rap1 localization in the cell is responsible for activation; it is also localized to the plasma membrane. 29 We have observed that out of 11 genes, eight genes, Rap1a, PKA, Nanog, ERK5/MAPK7, Oct-4, Rap1b, Epac1, and Con-43 were significantly upregulated, while Epac2, JNK/MAPK8, and ERK/MAPK1,…”
Section: Discussionmentioning
confidence: 99%
“…Integrin engagement with endogenous ligands can induce integrin clustering as signaling platform that recruits signaling molecules, such as cytoskeletal regulatory molecules, to form a signal transduction complex that regulates actin cytoskeleton assembly as well as morphological changes [39] . In addition, β 2 integrin engagement can activate Rac1, an essential cytoskeletal regulatory molecule belonging to the Rho family of small GTPases, through guanine nucleotide exchange factors (GEFs) [40] , [41] . Accumulating evidence indicates that Vav1 is one of three members of the Vav family (the others being Vav2 and Vav3), which is a well-studied family of GEFs for Rho GTPases [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that Se can influence leukocyte function both in vitro and ex vivo models. Intake of Se-enriched diet (0.3 mg/Kg diet) by goats has been associated with improvements in the function of the most abundant circulating phagocytic polymorphonuclear neutrophils, when compared with the selenium deficient diet (0.08 mg/kg diet) [78] , [79] , [80] , which are important players in the innate immune system [85] , [86] , [87] . It has been suggested that Se can protect against bacterial infections of bovine mammary gland by increasing the velocity of neutrophil migration to the site of the infection [77] .…”
Section: Se Involvement In the Immune And Inflammatory Responsesmentioning
confidence: 99%